Lipoprotein(a) levels in a sample of 115,197 subjects from the largest Brazilian private laboratory - Maria Helane Costa Gurgel Castelo; Isac de Castro; Priscila Raupp-da-Rosa; Patrícia Cristina Grenzi; Eduardo Gomes Lima; Andreza Almeida Senerchia; Érica Ferreira; Flavia Paiva Proença Lobo Lopes (PLoS ONE, 2025)
Lipoprotein(a) (Lp(a)) is an independent risk factor for atherosclerotic disease and is increasingly being incorporated into clinical algorithms of cardiovascular risk prediction. However, the epidemiology of Lp(a) in Brazil remains unknown. The objective of this study was to describe the distribution of Lp(a) levels and its association with laboratory parameters and clinical characteristics in a population of subjects submitted to blood tests in a private laboratory. Methods involved assessing Lp(a) levels from 115,197 subjects in a nationwide database from one Brazilian private laboratory, with Lp(a) measured using a nephelometric assay and expressed in mg/dL. Results showed that among the 115,197 subjects, the median age was 44 years. Women composed 61% of the sample and displayed higher Lp(a) levels in comparison to men (13.90 vs 11.58 mg/dL, p < 0.001). The distribution of Lp(a) levels was skewed rightward, as 70% of the individuals showed levels < 30 mg/dL, and 18% had levels higher than 50 mg/dL. The presence of criteria for diabetes, metabolic syndrome, and levels of HDL-cholesterol and triglycerides showed no correlation with Lp(a) levels. Additionally, there was no significant association between Lp(a) levels in individuals with and without criteria for diabetes and metabolic syndrome. In conclusion, this study represents the largest descriptive analysis of Lp (a) in Brazil, encompassing individuals with a wide age range and geographical distribution. This data contributes to the generation of high-quality evidence needed for improving cardiovascular risk assessment in clinical care settings.